Manajemen Syariah: Prinsip, Konsep, dan Implementasi - Muhammad Hafiz; Novien Rialdy (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Sharia business management is a management approach based on Islamic principles that prioritize justice, trustworthiness, and benefits. This article aims to discuss the concept, principles, and implementation of sharia business management and the challenges faced in its implementation. With a literature study approach, this article is expected to provide insight into the contribution of sharia management to ethical and sustainable business practices.